Morada UPF - Pelizzer, Jéssica Pagnoncelli (2022)
The Housing UPF arises from an academic experience, where the large majority of university students do not reside in the city of Passo Fundo, they need to make large daily movements and need a bigger support network that guarantees leisure, comfort and welcome during the period of academic training, in addition to promoting integration with the university, the equipment that the campus provides, and also reduce the costs of housing and transportation for students at the University Of Passo Fundo.